Desigualdade e transformações na distribuição de renda na Região Centro-Oeste do Brasil (2000-2010) - Cleverson Neves; Ednaldo Michellon; Umberto Antonio Sesso Filho (Confins)
The objective of this study is to analyze the transformations that occurred in the distribution of income and degree of social inequality measured by the Gini Index of the municipalities of the Midwest Region of Brazil in the period between 2000 and 2010 with data from the censuses carried out in the respective years. The methodology is based on the Exploratory Analysis of Spatial Data (AEDE) and the results make it possible to assess the evolution of income inequality in the region within the period of analysis and to identify patterns of clusters of municipalities (spatial clusters). The results show that the spatial clusters formed in the period of analysis do not differ significantly and show the persistence of income inequality between the localities, especially in the Upper-High groupings in the state of Goiás and in the Federal District, which indicate municipalities with high inequality neighboring others with the same characteristic. The increase in per capita income in the Midwest Region has not significantly changed the structure of income distribution in the municipalities, which implies the demand for public policies so that economic growth is accompanied by a process of income deconcentration.